Importance of human response in the administration and management of nursing care (Revista Electrónica Calidad en la Educación Superior, 2025)
Introduction: Nursing is a science and profession that provides care throughout life, from birth to death. It not only involves technical tasks but also encompasses the understanding of human responses to create personalized interventions, supported by the Nursing Process (NP). This process is essential in disease prevention and health promotion, extending beyond direct actions with individuals to being useful for the administration of health services and care management. Objective: To determine the importance of human response in the administration and management of nursing care. Methodology: A theoretical-reflective qualitative essay began with a review of indexed research in recognized databases, using keywords derived from Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH) in English, Portuguese, and Spanish. A critical reflection was then carried out on the main tenets of the most relevant articles regarding nursing care management and administration. The objective was to explore how understanding the human response can optimize health interventions within the administrative and management framework. Results and Discussion: The results indicate that care, the core of nursing, involves promoting health, preventing diseases, and rehabilitation. The Nursing Process (NP) adapts to individual needs and, although it focuses on direct care, its integration into care management and administration is crucial for decision-making. Administration organizes and controls resources, while management ensures their availability and coordination. Conclusion: Nursing’s ability to interpret human responses enables personalized care, but this skill is limited by a traditional biomedical perspective. Integrating this interpretation into health management could improve primary care, aligning with the goals of the WHO and PAHO. Nursing must play a key role in the administration of health services, promoting interdisciplinary leadership and equitable resource distribution through care management.
Keywords: Health Administration; Health Management; Health Promotion; Nursing; Nursing Care; Primary Prevention